(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The norms of the syntactic structure of sentences and word combinations have been improved, they become multifunctional and the scope of their use has been widened. They have their complex formation as well as the system. Currently, sentence structure and syntactic relations of words are used in a certain existing system. The presence of structural changes and deviations is legitimate, since the formation of the sentences is a complex process. Language elements that are the parts of the negative predicate, their differences, their specific properties, peculiarities of usage are considered in terms of the norm. The article also discusses the formation of negative predicates and their use in the language, the rules under which the negative predicates cannot transfer into the non-negative ones. Also, the sentences from works of art will be given as the examples. The syntactic system of the Kazakh language has gained significant stability. Other synonymous variants were selected in correspondence with the stylistic choice, the possibility of the combinability of words and the significance of thought in sentences has been raised. These achievements are based on proper language features, which were formed during the development of the literary language.